Tax Competition and Asymmetric Countries - Jevcak, Anton (Ekonomika, 2004)
This paper explores the consequences of a difference in the levels of public inputs accumulated over time in a small open economy model where capital tax revenues are used exclusively for the provision of public inputs, while the government sets the capital tax rate in way to maximise its country’s national income. It is shown that in this case the optimal capital tax rate in a country is a decreasing function of its stock of accumulated public inputs. The model thus implies that capital tax harmonisation could actually be detrimental to the so-called core EU member states as it could fix their capital tax rates at an in-optimally high levels and thus hinder their ability to dampen undesirable capital out- flows.